Kualitas Pelayanan Publik Dalam Pembuatan Kartu Identitas Anak Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Sidoarjo - Putri, Salsabilah; Pramudiana, Ika Devy (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2024)
This research aims to analyze the quality of public services in making children's identity cards at the Sidoarjo district population and civil registration service. Researchers used descriptive qualitative research methods. with several qualitative data collection techniques, namely; 1). interview, 2). observation, 3). documentation, and 4). focused discussion (Focus Group Discussion). In collecting data, researchers ensured that they combined several data sources for accuracy and reliability of results, namely from observations and interviews. Furthermore, when researchers carry out data analysis using qualitative research methods, it is very important to pay attention to the interpretation of the qualitative data. There are several stages in the data analysis carried out, data transcription, data categorization, data reduction, data description, data interpretation and reporting. In this study, researchers used the theory of Parasuraman, Zeithmal and Berry (Hardiansyah, 2018) that service quality can be measured using indicators, namely, Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The results of this article show that the quality of public services in making Child Identity Cards at the Sidoarjo Regency Population and Civil Registration Service needs to be improved through various factors such as efficiency, staff training, online systems, clear service standards, public input from, and priority on customer satisfaction. The discussion in this article emphasizes the importance of innovation and improving service quality to ensure public satisfaction in processing Child Identity Cards. It is also necessary to improve infrastructure, facilities and employee capabilities as well as implement quality service principles to improve the quality of KIA services.